Tridimensional Changes in Mandibular Arch after Rapid Maxillary Expansion Therapy: A Clinical Study - Giuseppina Laganà; Valeria Paoloni; Chiara Pavoni; Daniel Palmacci; Arianna Malara (Children, 2023)
Aim: The upper jaw transverse deficit is certainly one of the most common clinical issues in the orthodontic field. It can be due to skeletal or dental factors, and its etiology may be both genetic and environmental. Rapid maxillary expanders (RMEs) are certainly the most effective appliance for upper transverse deficiency correction. The aim of this study was to evaluate the changes that occurred in the mandibular arch during treatment with RMEs in growing subjects by analyzing tridimensional lower digital casts. Materials and Methods: The study group (SG) consisted of 20 subjects (10 M, 10 F; mean age 9.4 ± 2.8 years old) randomly selected at the Department of Orthodontics at the University of Rome, “Tor Vergata”. The inclusion criteria were negative posterior transverse interarch discrepancy ≥ 4 mm, mixed dentition phase with first permanent molars erupted, and prepubertal skeletal maturation stage (CS1-2), evaluated on a lateral radiograph through the Cervical Vertebral Maturation method. The SG was compared to an untreated control group (CG) of 20 subjects (10 M, 10 F, mean age 8.7 ± 2.3 years old) enrolled with the same inclusion criteria. The SG was treated by using RMEs. Dental casts of the lower arch were taken at two different times (T0–T1 = 6 months). All the dental casts were scanned with an OrthoXscan (Dentaurum 6mmbh E Co., Ispringen, Germany) and twenty points on the mandibular arch were digitized using Viewbox software. A Student t-test was used to compare the means of the quantitative variables associated with the effect of the device over time T0 and T1. Results: The results show a statistically significant increase (p < 0.05) in the intercanine and the intermolar diameters between the times T0 and T1 when compared to the CG. Conclusions: Rapid maxillary orthopedic expansion may achieve an increase in mandibular intercanine and intermolar diameter.